The Influence Of Psychological Factors On Stock Investment Decisions Among Millennials - Bailusy, Muhsin N.; Purwati, Sri; Nurriqli, Arifia; Zakaria, Zakaria; Ekaputra, Adriansyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Investment is the process of allocating capital or funds with the expectation of earning profits in the future. Psychological factors are of significant importance in the realm of investment decision making. A person may be influenced by psychological factors to make irrational investment decisions, which could cause a deviation from the desired level of risk and return as estimated by the investor. As a result, there is a need for a comprehensive examination of the psychological variables that can impact investment decision-making. Cognitive dissonance, herding, illusion of control, emotion, and overconfidence are the five variables examined in this research. The relationship between psychological factors and investment decision making can be predicted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique. The conclusion that the variables illusion of control, emotion, and overconfidence have a significant impact on investment decision making is supported by the PLS-SEM method's effective application in analyzing the influence of psychology on investment decision making. In the context of investment decisions, cognitive dissonance and herding variables exhibit negligible influence. Additionally, the predictive relevance value acquired in this research is greater than zero, suggesting that the variables and data effectively forecast the model with respect to the present state of affairs.